The cross-cultural adaptation and validation of the Nurse-Nurse Collaboration Scale in Italy: Nurse-Nurse Collaboration Scale in Italy - Marcomini, Ilaria; Pendoni, Roberta; Rosa, Debora; Locatelli, Giulia; Milani, Laura; Terzoni, Stefano; Celik Durmus, Serpil (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Collaboration between colleagues is an essential element of clinical nursing care because it helps to ensure patient safety. This study aimed to evaluate the psychometric properties of the XXX version of the Nurse-Nurse Collaboration Scale (NNCS). The secondary goal of this study was to assess the degree of collaboration between nurses in Italy. Methods: First, the cultural adaptation of the NNCS tool was performed. The face and content validity of the tool were assessed through the involvement of nursing experts. To test construct validity, a descriptive cross-sectional study was conducted on a sample of 362 nurses. Results: The Italian version of the NNCS was composed of 23 items distributed across five domains. The five-dimensional model showed an adequate model goodness of fit (RMSEA=0.075, CFI=0.883, SRMR=0.072). The NNCS dimension with the highest average score was Professionalism (M=3.10 ± 0.45), while Conflict Management (M=2.14 ± 0.47) exhibited the lowest score. Conclusions: The Italian version of the NNCS is a valid and reliable tool. More effort should be made to ensure the proper management of conflicts in healthcare environments.